Centre d'Art Contemporain Fri-Art Kunsthalle 1998-1999. - Ritter, Michel; Skenderovic, Damir; Zahm, Olivier; Fri-Art Centre d'Art Contemporain Kunsthalle, Fribourg (Fribourg : FRI-ART Centre d'Art Contemporain - Kunsthalle, 1999)
Puett, J. Morgan ; Khattari, Majida ; Kuratle, Sandra ; Dluzniewski, Piotr ; Haaning, Jens ; Jones, Sarah ; Krystufek, Elke ; Lesueur, Natacha ; Müller, Marianne ; Woodman, Francesca ; Aladag, Nevin ; Knorr, Daniel ; de Rijke, Jeroen ; de Rooij, Willem ; Boon, Elke ; Braeckman, Dirk ; Claerbout, David ; Meste, Philippe ; Smith/Stewart ; Land, Peter
Duits & Engels & Frans
boek